2008
DOI: 10.1021/jp709837r
|View full text |Cite
|
Sign up to set email alerts
|

High-Flux Ceramic Membranes with a Nanomesh of Metal Oxide Nanofibers

Abstract: Traditional ceramic separation membranes, which are fabricated by applying colloidal suspensions of metal hydroxides to porous supports, tend to suffer from pinholes and cracks that seriously affect their quality. Other intrinsic problems for these membranes include dramatic losses of flux when the pore sizes are reduced to enhance selectivity and dead-end pores that make no contribution to filtration. In this work, we propose a new strategy for addressing these problems by constructing a hierarchically struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 34 publications
0
29
0
Order By: Relevance
“…The resulting membrane has a pore size of 60 nm and consists of a titanate fiber intermediate layer and alumina fiber separation layer. [2,19] Their study clearly showed that the fiber separation layer offers high flux with excellent selectivity. Among the materials used for the preparation of ceramic membranes, titanium dioxide (TiO 2 ) is unique due to its excellent performance under UV irradiation on mineralization of a variety of organic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting membrane has a pore size of 60 nm and consists of a titanate fiber intermediate layer and alumina fiber separation layer. [2,19] Their study clearly showed that the fiber separation layer offers high flux with excellent selectivity. Among the materials used for the preparation of ceramic membranes, titanium dioxide (TiO 2 ) is unique due to its excellent performance under UV irradiation on mineralization of a variety of organic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Taking advantages of the highly porous fibrous nanostructures, ceramic nanofiber membrane can be used for filter and separator applications [128,[156][157][158][159]. separation layer on a porous substrate using large titanate nanofibers and smaller boehmite nanofibers [157].…”
Section: Filters and Separatorsmentioning
confidence: 99%
“…separation layer on a porous substrate using large titanate nanofibers and smaller boehmite nanofibers [157]. Traditional ceramic separation membranes, which are fabricated by applying colloidal suspensions of metal hydroxides to porous supports, tend to suffer from pinholes and cracks that seriously affect their quality.…”
Section: Filters and Separatorsmentioning
confidence: 99%
“…Despite these varieties, all TiO 2 membranes share a common asymmetric structural feature-a TiO 2 dense layer (responsible for selectivity) forms on the top of a porous membrane substrate (i.e., porous stainless steel, alumina or silica, responsible for providing mechanical and other supports) [5,12,14,15,17]. In order to obtain defect-free, crack-free and uniform TiO 2 selective layer, most of reported fabrication methods adopted tedious and costly multiple-coating strategies [3,17,18]. A common problem associated with current fabrication methods is the blockage of the pores of the porous membrane substrate, which can lead to a dramatic reduction in flux [3,5].…”
Section: Introductionmentioning
confidence: 99%
“…To solve the problem, intermediate layers must be formed with larger size TiO 2 precursor particles before the desirable size TiO 2 particle can be coated [3,5]. Though these measures have significantly reduced the blockage problem, the flux of the resultant membranes is low, attributing to the inherent disadvantages of random particle packing and the multi-intermediate layer structures [17,18]. Introducing the intermediate layers unavoidably increases thickness, leading to a decrease in flux.…”
Section: Introductionmentioning
confidence: 99%